“Incidencia del método Experimental como Estratégia didáctica para desarrollar el aprendizaje de ciencias naturales en los estudiantes de cuarto año de educación General Básica de la unidad educativa del milenio “Penipe”,ubicado en la provincia de Chimborazo, periódo marzo-junio 2015” - Once Chunata, Yolanda Elizabeth (2016)
This research was conducted at the Education Unit Millennium Penipe, Chimborazo Province with parallel fourth- year, "B", showing poor performance in the subject of Natural Sciences with an overall average of 6.35 (close to reaching follow-ups required), hence the need to design and implement the tutorial "Dieguito Learn Manipulating" with planned pilot projects according to the contents of Block IV and V program proposed by the Ministry of Education still important to relate the curricular components to improve teacher-student and develop skills, abilities and values interaction, this work is a contribution to education, to the institution, conscious of their role teachers and students in their comprehensive training, seeking to improve the quality of education. With regard to methodological aspect we worked with the non-experimental design, the type of research was applied, descriptive and explanatory level, process-based inductive-deductive which led to employ the technique of the survey with his instrument the questionnaire to a population of 25 students to collect information. The result of research indicates that met the research objective "To demonstrate how the application of the experimental method as a teaching strategy influences the development of learning of Natural Sciences" instrument validation that allowed test hypotheses raised was the chi square, application of the guidance improved the mutual learning process by 78% compared to 65% of initial performance for the above is recommended to use the guide as a strategy to facilitate learning.